Cairo : a graphic novel - Wilson, G. Willow, 1982- (Vertigo/DC Comics, 2007)
Set in bustling modern-day Cairo, this magical-realism thriller interweaves the lives of a drug runner, a down-on-his-luck journalist, an American expatriate, a young activist, an Israeli soldier, and a genie as they navigate the city's streets and spiritual underworld to find a stolen hooka sought by a wrathful gangster-magician.